A PERANCANGAN MEDIA PEMBELAJARAN PRAKARYA KELAS VII MENGGUNAKAN GOOGLE SITES - Indrianti, Zulka; Darmawati, Gusnita; Yuspita, Yulifda Elin; Annas, Firdaus (Information Technology Education Department, 2025)
This research is motivated by the difficulty of teachers in the learning process of workshops due to limited facilities and infrastructure, as well as higher student interest in technology-based learning media due to its accessibility. The purpose of this research is to design a workshop learning media for class VII using Google Sites at SMP Negeri 1 Lubuk Sikaping. The method used in this research is Research and Development (R&D) with Luther Sutopo's Multimedia Development Life Cycle (MDLC) development model. This model consists of six stages: conception, design, material collection, assembly, testing, and distribution. The results showed that the designed learning media was declared valid, practical, and effective based on the product test results. The validity test resulted in an average score of 0.82 (valid category), the practicality test obtained an average score of 0.89 (very high category), and the effectiveness test obtained an average score of 0.84 (high effectiveness category). It is expected that this learning media can improve the quality of workshop learning, provide convenience for teachers, and motivate students in the learning process. The implication of this research is that the integration of technology in learning can be an innovative solution to overcome the limitations of facilities and infrastructure, while encouraging the creation of more interesting and effective learning.